Psicanálise e hermenêutica em Paul Ricoeur: da suspeita ao sentido, da fantasia ao símbolo - Carré, Douglas Moisés Pinheiro (2017)
This research shows how Paul Ricoeur (1913-2005) incorporates some concepts and, above all, the spirit of freudian psychoanalysis to the hermeneutic philosophy. Ricoeur notes that there is, in Freud, a hermeneutic of suspicion that puts at risk the whole philosophy and culture that had been built and founded on the certainty of Cartesian cogito. Our author believes the passage by Freud, accepting his questions and incorporating his learning, is imperative to Philosophy and to the contemporary philosopher. However, Ricouer does not only invite us to suspicion but also invites us to hear it. The conflict between the hermeneutics of suspicion and the restoration of meaning, is the intent of our philosopher, namely: reaching a second moment of interpretation, a second innocence in and by the critics. If there is a school of suspicion, there is also of confidence, belief and faith. Freud, Nietzsche and Marx lead Ricoeur to suspicion, however it goes beyond, because he wants to see emerge a post-critical faith able to comprehend the questions, above all, Freudianism, allowing them to question the point of reducing the masks and the illusions of consciousness so that the sense comes. The proposal of Ricoeur is then left for a hermeneutics of the symbol that assumes the passage by critics of the masters of suspicion and that is a real bug in symbol, but now, no more naive and based on immediate consciousness, bearing and donor of sense, but a critical and instructed listening that takes into account the reflections and the discoveries of psychoanalysis of Freud. At the end of our research we will cover some classical texts of Freud who plays the basic themes of religion, in order to read them from Ricoeur and his interpretative dialectic, aiming at elucidating more explicitly as our philosopher incorporates the suspicion to the hermeneutics of the restoration of meaning.